The Value of the Effect of the Level of Specific Antibodeis on Elimination Different Tick-Borne Encephalitis Virus Strains - G. N. Leonova; V. A. Lubova; A. V. Kalinin (Эпидемиология и вакцинопрофилактика)
We have shown the levels of specific antibodies that can neutralize different strains on the virulence of the virus of tick-borne encephalitis (TBE). Specific immunoglobulin with its titers of 1:100, 1:400 и 1:3200 and two TBEV strains with its doses 3 lg TCID50/ ml (Dal negorsk - highly pathogenic, Primorye-437 - not pathogenic for humans). Evidential basis of the activity of residual virus has been obtained in vitro and in vivo in 3, 24, 48 and 72 hours after infection cells of culture PK and mice neinbrednyh by the test samples. Immunoglobulin does not have a protective effect, if its titer is 1:100; inhibits low virulent strain (P-437), but not Dal negorsk one, if its titer is 1:400; and inhibits both strains, it its titer is 1:3200. Regarding the models of different TBE virus strains, this article suggests new approaches to studying the efficacy of specific vaccine prophylaxis and individual prescription of the amount and terms of revaccination for tick-borne encephalitis.